Level of Creativity and Entreprenuership Potentials among Undergraduates in Kwara State, Nigeria - YAHAYA, Lasiele Alabi; AMINU, Hammed Popoola (Ilorin Journal of Education, 2025)
The level of unemployment in Nigeria among youth is well perceived in every nook and cranny of the country. This has become a major concern of education stakeholders in the recent time, leading to increased efforts on how undergraduates will gainfully employed after graduation. Hence, this study focused on level of creativity and entrepreneurship potentials among undergraduates in Kwara State. The study utilized correlational design and instruments tagged “Undergraduates Creativity Questionnaires” (UCQ) and Undergraduates Entrepreneurship Potentials Questionnaires (UEPQ), to collect data for the study. The instrument was validated among five senior lecturers in the field of counselling/psychology. The reliability test was conducted using test-retest methods which yielded reliability coefficients of 0.76 and 0.72 respectively. Data collected were analyzed using frequency count, percentage, mean and rank order, and PPMC was used to test the hypotheses of the study at 0.05 level of significance. The findings of the study revealed that the participants of the study possessed a moderately high level of creativity, and moderate chances of leading the economy to prosperity in the nearest future for moderately possessing entrepreneurship potentials required for job creation. It is also discovered that there was a positive relationship between undergraduates’ creativity and their entrepreneurship potentials. Based on the findings of this study, it was recommended among other things that, each university should align their curricular as a matter of urgency, in such a way that will help their students to be self-reliant after graduation.